An Innovative Approach to the Development of Project Management Processes for Small‐scale Projects in a large Engineering Company. (28th October 2015) - Laporte, Claude Y.; Chevalier, Frédéric
Abstract: A Canadian division of a large American engineering company has developed and implemented project management processes for their small‐scale and medium‐scale projects. The company was already using a robust project management process for their large‐scale projects. The objectives of this process improvement project were to reduce cost overruns and project delays, standardize practices to facilitate the integration of new managers, increase the level of customer satisfaction and to reduce risk‐related planning deviations. For this improvement project, the engineering organization used the new ISO/IEC 29110 standard developed specifically for very small entities. An analysis of the cost and the benefits of the implementation of small and medium scale project management processes was performed using the ISO economic benefits of standard methodology. The engineering enterprise estimated that, over a three‐year timeframe, savings of about 780, 000$ would be realized due to the implementation of project management processes using the ISO/IEC 29110 standard.